The Teachers’ Training College/Institute of Education Library in post war Singapore, 1950-1991: a historical perspective - Lim, Peng Han (Malaysian Journal of Library and Information Science, 2017)
Han, L. P. (2012). The Teachers’ Training College/Institute of Education Library in post war Singapore, 1950-1991: a historical perspective. Malaysian Journal of Library & Information Science, Vol.17, no. 1: 93-106. This article is a study on the historical development of the Teacher’s Training College (TTC) library in two phases. From 1950 to 1973 it was known as the TTC library and from 1973 to 1991 it became the Institute of Education (IE) library after the TTC was converted into the IE. It refers widely to the annual reports of the TTC and IE and other official education reports to have an in depth understanding of the historical development of the library. Throughout the two phases of development study identifies the lack of recruitment and deployment of professional library staff to manage a specialized education library. By retrieving specific data from official library surveys the study shows how the collection of the library evolved from print to include non-print items during the years 1964, 1969, 1975, 1983 and 1989 and the gradual progress being made to improve its collection. The second phase of the library shows how the Library set up its organization structure and adopted the use of information technology and the implementation of an integrated library management system.